MANAJEMEN KEPEMIMPINAN KEPALA SEKOLAH DALAM PENINGKATAN KOMPETENSI PEDAGOGIK GURU SD NEGERI 021 SUNGAI KUNJANG SAMARINDA : MANAJEMEN KEPEMIMPINAN KEPALA SEKOLAH DALAM PENINGKATAN KOMPETENSI PEDAGOGIK GURU SD NEGERI 021 SUNGAI KUNJANG SAMARINDA - Ratnasari, Wienda; Komariyah, Laili; Masruhim, Amir; Gede Mulawarman, Widyatmike; n, Nurlaili; Dwiyono, Yudo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
School principal leadership management is important in the process of managing and leading school resources to improve teacher competence and learning quality effectively through planning, organizing, implementing, and evaluating. The purpose of this study is to describe the planning, organizing, implementing, and supervising carried out by the principal in improving teachers' pedagogical competence at SD Negeri 021 Sungai Kunjang, Samarinda City. This study uses a qualitative approach with a case study method. Data were collected through in-depth interviews, observations, and documentation involving the principal, teachers, and other related parties. Data analysis was carried out interactively through stages of data collection, data reduction, data presentation, and conclusion drawing. To maintain data validity, the researcher used source triangulation and technique triangulation techniques. The results of the study show: 1) The principal's leadership planning in improving teachers' pedagogical competence by collecting data from teacher performance evaluations. 2) Organization is carried out through a clear division of tasks, coordination with school partners, and the empowerment of senior teachers as mentors to support teacher professional development, 3) Implementation includes technical guidance programs, in-house training, learning communities, webinars, and independent training on the Merdeka Mengajar platform, supported by regular academic supervision. 4) Supervision in the form of monitoring and evaluation is carried out periodically through classroom observation, evaluation meetings, monitoring, and constructive feedback for continuous improvement of the teacher competency improvement program. The principal actively provides guidance and supervision, and develops a data-based evaluation system for a more effective teacher competency development program